New approach for the Fornberg-Whitham type equations - Boutarfa, Bariza; Akgul, Ali; İnç, Mustafa (Elsevier Science Bv, 2017)
This paper applies the reproducing kernel Hilbert space method to the solutions of three types of Fornberg-Whitham equations: original, modified and time fractional. Comparison with Adomian decomposition method, homotopy analysis method and the variational iteration method shows the validity and applicability of the technique. (C) 2015 Elsevier B.V. All rights reserved.
International Conference on Mathematical and Computational Modelling in Science and Technology -- AUG 02-07, 2015 -- Izmir Univ, Izmir, TURKEY
Keywords: Reproducing kernel method; Series solutions; Fornberg-Whitham equations